2005
DOI: 10.1002/jnr.20438
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced up-regulation of activated macrophages in the degenerating taste system

Abstract: Unilateral chorda tympani (CT) nerve section and maintenance on a sodium-restricted diet leads to a rapid decrease in neurophysiological taste responses to sodium in the contralateral, intact CT nerve. Up-regulation of immune function with lipopolysaccharide (LPS; 100 microg i.p.) induces a recovery of normal sodium taste responses, suggesting that the sodium-deficient diet is immunosuppressive. In fact, there is a bilateral increase in the number of lingual, activated macrophages in control-fed rats receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 44 publications
2
48
2
Order By: Relevance
“…Previous research demonstrated that sodium restriction leads to an attenuation of chorda tympani nerve responses to sodium salts when combined with nerve or lingual epithelial injury, also resulting in an attenuated lingual macrophage response to injury (6,7,22,32,33,39). Stimulating the immune response with LPS injections eliminates these differences (6,39).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous research demonstrated that sodium restriction leads to an attenuation of chorda tympani nerve responses to sodium salts when combined with nerve or lingual epithelial injury, also resulting in an attenuated lingual macrophage response to injury (6,7,22,32,33,39). Stimulating the immune response with LPS injections eliminates these differences (6,39).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, aldosterone suppressed the bilateral macrophage response to neural injury. Control staining, in which the primary antibody was omitted or an isotype-matched irrelevant antibody was substituted (not shown), showed minimal nonspecific immunoreactivity (6,32).…”
Section: Neurophysiologymentioning
confidence: 98%
See 3 more Smart Citations